A Plasmodium berghei sporozoite-based vaccination platform against human malaria - Mendes, AM; Machado, M; Gonçalves-Rosa, N; Reuling, IJ; Foquet, L; Marques, C; Salman, AM; Yang, ASP; Moser, KA; Dwivedi, A; Hermsen, CC; Jiménez-Díaz, B; et al. (Springer Nature, 2018)
There is a pressing need for safe and highly effective Plasmodium falciparum (Pf) malaria vaccines. The circumsporozoite protein (CS), expressed on sporozoites and during early hepatic stages, is a leading target vaccine candidate, but clinical efficacy has been modest so far. Conversely, whole-sporozoite (WSp) vaccines have consistently shown high levels of sterilizing immunity and constitute a promising approach to effective immunization against malaria. Here, we describe a novel WSp malaria vaccine that employs transgenic sporozoites of rodent P. berghei (Pb) parasites as cross-species immunizing agents and as platforms for expression and delivery of PfCS (PbVac). We show that both wild-type Pb and PbVac sporozoites unabatedly infect and develop in human hepatocytes while unable to establish an infection in human red blood cells. In a rabbit model, similarly susceptible to Pb hepatic but not blood infection, we show that PbVac elicits cross-species cellular immune responses, as well as PfCS-specific antibodies that efficiently inhibit Pf sporozoite liver invasion in human hepatocytes and in mice with humanized livers. Thus, PbVac is safe and induces functional immune responses in preclinical studies, warranting clinical testing and development.